Eating Disorders and the Skin - Strumia, Renata (Springer Berlin Heidelberg : Imprint: Springer, 2013)
At least 40 skin signs are associated with eating disorders (EDs), and some of them are considered guiding signs because they are indicative of an otherwise hidden ED. These skin signs may arise due to starvation, self-induced vomiting, drug consumption, and concomitant psychiatric illness. The role of the dermatologist in this context is to suspect the presence of a hidden ED based on the guiding signs. With this in mind, the most important specialists in the field come together in this book to document all of the dermatological aspects of EDs. General topics such as classification of EDs, epidemiology, and medical complications are first addressed, and skin signs attributable to various causes are then discussed in a series of detailed chapters. Characteristic changes in the hair, nails, and oral cavity are also carefully documented. The closing chapters address various other related issues of interest, including pain sensitivity in patients with EDs and the effects of anorexia nervosa on skin thickness and skin collagen. Eating Disorders and the Skin will be an invaluable source of up-to-date information for both novice and experienced dermatologists, as well as other practitioners with an interest in EDs, psychiatrists, and nurses.